Drought resistance of winter soft wheat samples in the primary phase of organogenesis and change of leaf area and chlorophyll content in leaves under the conditions of water stress - V. A. Likhovidova; Е. V. Ionova; V. L. Gaze; D. М. Machenko (Зерновое хозяйство России, 2018)
There has been conducted laboratory assessment of drought resistance of winter soft wheat samples on an osmatic solution (sucrose 16 atm.). The maximum values of this indicator ranged from 70.0% (“Lidiya”) to 79.3% (“Asket”). According to the results of vegetation trials, it was established that in conditions of insufficient moisture supply (aridity of 30% PV) during the flowering phase, the total leaf area of winter wheat varieties and lines varied from 45.2 cm2 (“Volny Don”) to 63.4 cm2 (“Kazachka”), and in the phase of milky ripeness of grain, the total leaf area ranged from 3.5 cm2 (“260/09”) to 17.7 cm2 (“Polina”). The varieties “Krasa Dona”, “Kapitan”, “Lidiya”, “Asket” showed the best ratio of the upper leaves area to the lower ones under arid conditions (in favor of the upper ones in the flowering phase). In the phase of milky ripeness, the presence of lower green leaves was identified in the varieties “Kapitan”, “Krasa Dona”, “Izyumnka”. The amount of accumulated pigments (chlorophyll) in the leaves remains the highest during the flowering period and the milky ripeness of the grain in the varieties “Kapitan” (3.1 and 2.6 m/100g of dry matter), “Kazachka” (2.9 and 2.4 mg/100g of dry matter), “Krasa Dona” (2.8 and 2.4 mg/100g of dry matter), “Asket” (2.7 and 2.3 mg/100g of dry matter), “Lidiya” (2.6 and 2.4 mg/100g of dry matter), “Izyumnka” (2.5 and 2.1 mg/100g of dry matter).